Three-Dimensional Excitation and Emission Fluorescence-Based Method for Evaluation of Maillard Reaction Products in Food Waste Treatment - Jiaze Liu; Jun Yin; Xiaozheng He; Ting Chen; Dongsheng Shen (Journal of Chemistry)
Hydrothermal treatment (HT) of food waste (FW) can form Maillard reaction products (MRPs), the biorefractory organic matter due to the occurrence of Maillard reaction. However, the integrating qualitative and quantitative approach to assess MRPs is scarce. The goal of this study was to develop a method to characterize and quantify MRPs created by HT of FW. MRPs were identified by molecular weight fractionation, indirect spectrometric indicators, and three-dimensional excitation-emission fluorescence (3DEEM) analysis. The 3DEEM method combined with fluorescence regional integration (FRI) and parallel factor (PARAFAC) analyses was able to differentiate clearly between MRPs and other dissolved organic compounds compared to other approaches. The volume of fluorescence Φ from FRI and maximum fluorescence intensity Fmax from PARAFAC were found to be suitable quantitative parameters for determination of MRPs in the hydrothermal FW system. These two parameters were validated with samples from hydrothermal FW under various operating temperatures and pH.